GaAs-filled elliptical core-based hexagonal PCF with excellent optical properties for nonlinear optical applications. Issue 4 (15th February 2022) - Amin, Ruhul; Abdulrazak, Lway Faisal; Mohammadd, Noor; Ahmed, Kawsar; Bui, Francis M.; Ibrahim, Sobhy M.
Abstract: This manuscript comes up with a unique GaAs-filled elliptical core-based hexagonal cladding PCF that manifests ultra-high birefringence (Br) and non-linear coefficient (NLC). The distinct optical characteristics of the PCF are thoroughly simulated and analyzed by the finite element method (FEM) through the commonly available COMSOL Multiphysics software. The simulated findings confirm that using the high refractive index (RI) advantages of GaAs at the effective wavelength of 1.55 μ m, a high Br of 0.92, as well as an ultra-high NLC of 2.06 × 10 6 W − 1 K m − 1 and zero-dispersion can be obtained. Besides, several primary optical properties, namely numerical aperture (NA), confinement loss (CL), power fraction (PF), dispersion, etc. are also discussed and investigated in depth in the propounded article. The zero-dispersion characteristic, as well as the high Br and ultra-high NLC of the advanced PCF model, make it a worthy candidate for extensive purposes, including biochemical detection, high nonlinear applications, supercontinuum generation, optical communication and other sensing applications.